PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN SEBAGAI VARIABEL MODERATING (Studi Kasus di Percetakan MK Digital Printing) - Ayu Lestari; Mhd. Irwan Padli Nasution; Nur Ahmadi Bi Rahmani (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
Facilities and service quality are important things that must be considered by companies engaged in services. The existence of good facilities and service quality in the minds of consumers will create a good image so that consumers become generous with the services provided by the company. This study aims to determine the effect of facilities and service quality on customer loyalty with satisfaction as a moderating variable (a case study in the Constitutional Court Digital Printing). This study uses a quantitative approach. The population of 2969 in this study were customers who had used the services of the Constitutional Court Digital Printing. The sample used was 97 respondents and questionnaires as a means of collecting data for respondents. The analytical method used in this research is validity test, reliability test, classical assumption test and Moderated Regression Analysis (MRA) test. The results of this study indicate that facilities, and service quality have a significant influence on customer loyalty at MK Digital Printing and the effect is from Variable X1, namely facilities and customer satisfaction which have the effect of increasing the influence of facilities on customer loyalty. Thus, that the result of the satisfaction variable is a moderating variable or can be used as an independent variable as well as a moderator variable.